2014
DOI: 10.11114/ijsss.v2i2.309
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Cross-cultural Adaptation and Validation of the Malay Version of the Maslach Burnout Inventory (MBI) in Malaysia

Abstract: The Maslach Burnout Inventory (MBI) has been widely used in research for more than 2 decades and is recognized as the leading measure of burnout. Malaysia is a multi-ethnic country and English is regarded as the second language. Therefore, it is essential to have a culturally acceptable translated Malay version of MBI, which can easily be understood by Malaysians, in order to study the burnout level in our population. Hence, the objectives of this study are to translate, cross-culturally adapt and validate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…But our analysis suggested that items 8, 9, and 13 of the scale should have been located in the exhaustion rather than cynicism subscale. The same issue has been mentioned in the Malaysian version, and authors suggested it to be mainly the result of differences in cultural knowledge and experience [15]. However, both of Japanese [13] and Chinese versions [16] have supported the original version.…”
Section: Vietnamese Versions Of the Mbi-gs And Awsmentioning
confidence: 81%
See 1 more Smart Citation
“…But our analysis suggested that items 8, 9, and 13 of the scale should have been located in the exhaustion rather than cynicism subscale. The same issue has been mentioned in the Malaysian version, and authors suggested it to be mainly the result of differences in cultural knowledge and experience [15]. However, both of Japanese [13] and Chinese versions [16] have supported the original version.…”
Section: Vietnamese Versions Of the Mbi-gs And Awsmentioning
confidence: 81%
“…The MBI-GS and AWS are well used in the domain of occupational health research. The translated versions of MBI-GS exist such as the Japanese version [13], Malaysian version [15], and Chinese version [16], even in Asian countries. The Vietnamese version we created in the present study would be useful to develop occupational health research in Vietnam.…”
Section: Vietnamese Versions Of the Mbi-gs And Awsmentioning
confidence: 99%
“…(Kozak et al, 2013) found that five psychosocial factors strongly associated with personal burnout were emotional demands, work-privacy conflict, role conflict, job insecurity and feedback at work. Majority of the previous studies done investigating burnout among academicians used the Maslach Burnout Inventory (MBI) (Al-Mobeeriek, & Al-Mobeeriek, 2011;Chen et al, 2014;Otero-López, Mariño, & Bolaño, 2008;Padilla & Thompson, 2016). In a local study involving academicians from private universities in Malaysia revealed that 6% of the participants have burnout characteristics using the MBI (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequently, certain researchers have suggested removing the weakerperforming items from the scale in order to improve the goodness of fit parameters, while some others believe that factor structures different to the threedimensional one would be more suitable (11). Items 6, 12-13, 16 and 20 have been found to either deviate from their original sub-scale or the model has been found to be better with those deleted (11)(12).…”
Section: Introductionmentioning
confidence: 99%